1978
DOI: 10.1093/ptj/58.11.1355
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Goniometric Measurements

Abstract: This study determined the intratester and intertester variability and reliability of goniometric measurements taken by four physical therapists on upper and lower extremity motions of normal male subjects. The same subjects were measured once weekly for four weeks by testers with varied experience in goniometry. Data were analyzed by analyses of variance with repeated measures. Intratester variation for all measurements was less than intertester variation. Further, intertester variation was less for the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
257
3
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(281 citation statements)
references
References 0 publications
12
257
3
9
Order By: Relevance
“…The measurement error for joint motion, reported in the literature, varies between the different movements measured and the position of the subject (Bierma-Zeinstra et al 1998;Boone et al 1978;Ekstrand et al 1982). Boone et al (1978) reported an average measurement error of 3.78 and concluded that individual variation in active lower limb 160 K. Hagberg et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement error for joint motion, reported in the literature, varies between the different movements measured and the position of the subject (Bierma-Zeinstra et al 1998;Boone et al 1978;Ekstrand et al 1982). Boone et al (1978) reported an average measurement error of 3.78 and concluded that individual variation in active lower limb 160 K. Hagberg et al…”
Section: Discussionmentioning
confidence: 99%
“…Boone et al (1978) reported an average measurement error of 3.78 and concluded that individual variation in active lower limb 160 K. Hagberg et al…”
Section: Discussionmentioning
confidence: 99%
“…The arms of the goniometer should be aligned, with the proximal arm along the midline of the fibula, the fulcrum by the lateral malleoli and the distal arm parallel to the fifth metatarsal (Norkin and White, 1985). Regular goniometric range of motion evaluations have been shown to be reliable, with intra-tester reliability being higher than inter-tester reliability (Boone et al, 1978, Rothstein et al, 1983. HaglundÅkerlind and Eriksson (1993) used ankle range of motion in an hydraulic isokinetic dynamometer to obtain a more objective measure of muscle flexibility.…”
Section: Physical Examinationmentioning
confidence: 99%
“…Because of its widespread use in orthopedics, the reliability of goniometric assessment (continuous data) has been rigorously investigated. [6][7][8][9] Clinicians also utilize pass/ fail (or negative/positive) scoring systems (dichotomous data) to assess ROM about a particular joint. These orthopedic tests (sometimes referred to as ''special tests'') help to determine whether a particular type of dysfunction (i.e., impingement syndrome, agonist/antagonist imbalance in muscle strength or flexibility, etc.)…”
mentioning
confidence: 99%